A study of the process and barriers of property tax revenue generation in local government (a case study of Pasir Gudang Municipal Council) - Umar, Mohammed Akilu (2013)
Property tax collection issues in local governments are an important area of concern in recent years. Similarly, Pasir Gudang Municipal Council is facing serious challenges due the accrual of arrears on property tax. These issues are directly linked to the conducts and compliance behavior of the taxpayers which determine the revenue generation of the local government. Therefore, as a result of high non-compliance behavior of the taxpayers, the revenue generation capacity of Pasir Gudang Municipal Council has been declining. This study therefore, makes an effort to investigate the problems of low property tax revenue generation at Pasir Gudang Municipal Council, Malaysia. Random sampling technique was used for the data collection required for the study. Nevertheless, the study adopted a mixed method approach. 300 respondents are targeted which form the sample size to answer one of the research questions. While the qualitative method answers the other 3 research questions. However, 264 questionnaires were returned. The quantitative data analysis employed was simple distribution tables, bar chart and percentage distribution. On the other hand, thematic network analysis and narration, photographs and observations were used for qualitative analysis. The study has discovered that inadequate provisions of infrastructural facilities and services are the reason for the decline in property tax revenue collection generation in the study area. Because the findings of study discovered that the taxpayer's expectations were to have adequate infrastructural facilities and services in the study area but due to the absence of these requirements most of them evade paying the property tax. Through the findings of the study a relationship between public authorities and the taxpayers is established. The research contribution to knowledge based on the findings of this study is very significant. The study has established that provision of public amenities (public goods and services) is a determinant to taxpayers compliance. This can be used as an extension on Fischer's model of compliance behavior. However, effective public engagement in the public service delivery and enforcement could yield positive results.